Knee Cartilage and Subchondral Bone Evaluations by Magnetic Resonance Imaging Correlate with Histological Biomarkers in an Osteoarthritis Rabbit Model. (August 2022) - Sifre, Vicente; Ten-Esteve, Amadeo; Serra, C. Iván; Soler, Carme; Alberich-Bayarri, Ángel; Segarra, Sergi; Martí-Bonmatí, Luis
Objective: To evaluate pathological changes in cartilage and subchondral bone MRI biomarkers in a rabbit model of osteoarthritis (OA) and correlate these with histological variations. Design: Transection of the anterior cruciate ligament was performed on the right knee of eighteen 12-week-old New Zealand white rabbits to induce OA. 3-Tesla MR images were obtained from 18 healthy control knees (left) and 18 knees with OA (right). Imaging biomarkers included volume, thickness, T1 and T2* cartilage parametric maps, and several subchondral bone features: bone volume to total volume ratio, trabecular thickness, trabecular spacing, trabecular number (TbN), 2D and 3D fractal dimensions, and quality of trabecular score (QTS). Microscopic analysis of the lateral femoral condyles was set as the ground truth. Results: When healthy and osteoarthritic knees were compared, significant differences were seen in the T1 and T2* values of the femur and tibia cartilage and in the subchondral bone volume to total volume, TbN, and QTS of both the lateral and medial aspects of the femur and tibia. Histological findings revealed significant osteoarthritic changes between healthy and osteoarthritic knees in stain, structure, chondrocyte density, total score, and subchondral bone biomarker levels. A positive correlation was found between histological staining, structure, chondrocyte density, and total score variables in T1 and T2* cartilage biomarkers. A negative correlation was observed between histological subchondral bone variables and magnetic resonance D2D and QTS biomarkers. Conclusion: Quantification of several cartilage and subchondral bone imaging biomarkers in a rabbit model of OA allows the detection of significant changes, which are correlated with histological findings.